Pengaruh Kepuasan Kerja dan Stres Terhadap Tingkat Produktivitas Karyawan Bagian Pemasaran Pada PT. Jessindo Prakarsa Bogor - Rizman Rifqie; Astriana Prama Shinta (STIE Binaniaga, 2009)
Job satisfaction is an emotional attitude of fun and loved his work, and thus will reflect the attitude of discipline and work performance. Satisfaction is a combination of inside and outside the company that reflects the balance between the remuneration to be received by the execution of his work. Employee productivity also related to the right of labor to obtain the potential development opportunities that exist in self-employees in accordance with the capabilities (education) and experience in order to increase its productivity. By knowing satisfaction and job stress of employees by the company it is expected that employye productivity can be measured. The results show the following (1) Index based on the work kepusasan satisfaction index score of 51.51 the respondent’s answer has categorized job satisfaction of employees in PT. Jessindo Prakarsa satisfied (2) stress index based on the stress index value of 63.38 then categorized the respondent’s answers have the stress of employees in PT. jessindo Prakarsa in very high. (3) the productivity of employees is measured by pencapian sales targets set by the company to each of the sales force in August 2008. With the scale realization of the sales of each salesperson is used to calculate the productivity level of each individual in the marketing of PT. Jessindo Prakarsa, average labor productivity of the marketing department employee in August 2008 amounted to 72.38% (considered good). Effect of stress on job satisfaction and work productivity at PT. Jessindo Prakarsa, with a sig value of 0.004 <a = 0.05 in other words there is the influence of job satisfaction and stress together on the level of productivity at PT Jessindo Prakarsa